Front Cover: Generation and Reaction of Functional Alkyllithiums by Using Microreactors and Their Application to Heterotelechelic Polymer Synthesis (Chem. Eur. J. 60/2019). Issue 60 (4th September 2019) - Nagaki, Aiichiro; Yamashita, Hiroki; Tsuchihashi, Yuta; Hirose, Katsuyuki; Takumi, Masahiro; Yoshida, Jun‐ichi
Abstract : A few‐millisecond chemistry approach, conducting a series of reactions with short‐lived intermediates in a flow microreactor, enabled chemical conversions involving alkyllithiums bearing an electrophilic functional group, which are virtually impossible with conventional macro batch reactors. Controlling such reactions are extremely difficult, because the functional groups readily react with alkyllithiums. A built‐in type flow microreactor system was specifically designed and constructed for these transformations, achieving milliseconds chemistry. More information can be found in the Full Paper by A. Nagaki, J.‐i. Yoshida, et al. on page 13719 .